2015
DOI: 10.5539/jms.v5n1p192
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture, Motivation, Job Satisfaction and Performance of Employees toward the Implementation of Internal Bureaucracy Reform in the Ministry for the Empowerment of State Apparatus and Bureaucracy Reform (The Ministry of Panrb)

Abstract: Implementation of bureaucratic reform agenda in a government agency is determined by the culture of the organization and human resources of the institution. This study aimed to discover how organizational cultural relations, motivation, job satisfaction, and performance of the bureaucracy reform internally perceived by the employees at the Ministry of PANRB. This study used a qualitative approach. One of the sources of data is surveys conducted by the Ministry of PANRB. The results showed that employee satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Sejalan dengan hal ini, beberapa penelitian menyatakan bahwa budaya organisasi berpengaruh terhadap kinerja guru (Karantiano, 2013), serta ada efek positif (Ismiyarto, Suwitri, Warella, & Sundarso, 2015), (Arifin M., 2015) dan efek signifikansi terhadap kinerja guru (Udin, Luva, & Hossian, 2013). Ini berarti bahwa peran budaya organisasi sangat penting dalam menentukan keberhasilan guru untuk meningkatkan penampilannya.…”
Section: H2: Pengaruh Budaya Organisasi Terhadap Kinerja Guruunclassified
“…Sejalan dengan hal ini, beberapa penelitian menyatakan bahwa budaya organisasi berpengaruh terhadap kinerja guru (Karantiano, 2013), serta ada efek positif (Ismiyarto, Suwitri, Warella, & Sundarso, 2015), (Arifin M., 2015) dan efek signifikansi terhadap kinerja guru (Udin, Luva, & Hossian, 2013). Ini berarti bahwa peran budaya organisasi sangat penting dalam menentukan keberhasilan guru untuk meningkatkan penampilannya.…”
Section: H2: Pengaruh Budaya Organisasi Terhadap Kinerja Guruunclassified
“…First, Villa et al (2003) posit that, to fully understand construct related to performance and leadership, OC should be considered as a situational variable. Second, research has found that the harmonious combination of appropriate leadership behaviours with certain types of OCs can positively influence employees' performance (Ismiyarto et al, 2015;Ogbonna and Harris, 2000). Third, culture is one of the major sources of nurturing and developing new ideas in an organization (Uzkurt et al, 2013).…”
Section: Strategic Improvisation and Organizational Performancementioning
confidence: 99%
“…The successful of organization depends on employee performance (Ismiyarto et al, 2015). Individual performance is influenced by factors of knowledge, skills, motivation and role of the individual concerned.…”
Section: Theoritical Reviewmentioning
confidence: 99%